Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1108/jfbm-10-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the research field of corporate social responsibility in family firms: a citation analysis

Abstract: Purpose Inspired by increasing public interest in corporate social responsibility (CSR) and the intensified focus of research on family firms (FFs) over the past few decades, the purpose of this paper is to analyze the existing literature on CSR in FF through a citation analysis. Design/methodology/approach This paper overviews the structure of research on CSR in FF, identifying influential publications, authors, and key lines of discussion. The authors identified the underlying sample through a systematic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 124 publications
(302 reference statements)
1
6
0
Order By: Relevance
“…The most noticeable indicator is charitable contributions, which are given to various social actions, sports, culture and health. Therefore, the family businesses included in the sample engaged in this activity; the correlation between the family business characteristics and SR are in accordance with previous studies [68,69], but unexpectedly, the correlation of management with the SR was not identified, knowing that M is mandate to carry out the expenditure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most noticeable indicator is charitable contributions, which are given to various social actions, sports, culture and health. Therefore, the family businesses included in the sample engaged in this activity; the correlation between the family business characteristics and SR are in accordance with previous studies [68,69], but unexpectedly, the correlation of management with the SR was not identified, knowing that M is mandate to carry out the expenditure.…”
Section: Discussionsupporting
confidence: 83%
“…Even if many family businesses do not have an extended corporate governance structure, most family members have decided to be socially responsible. The relationship between CSR and family firms was studied in many research papers, and the results were heterogeneous [68] and highly segmented and unstructured [69].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, different scholars have called for further CSR research within family firms under different focal points (e.g. Berrone et al, 2010;Van Gils et al, 2014;Preslmayer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Research on CSR in family firms has increased significantly over the last few years, and the related research field is growing (Faller and zu Knyphausen-Aufseß, 2018 ; Kuttner & Feldbauer-Durstmüller, 2018 ; Mariani et al, 2021 ; Preslmayer et al, 2018 ). Due to the variety of studies, the opportunity has come to synthesize the current state of research so that future research can depart from a common understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, the literature shows that current research often suffers from a misalignment between empirical research and theory. The prevailing assumption is that family objectives drive family firm CSR activities (Preslmayer et al, 2018 ), thereby obtaining family and firm outcomes, whereas family firm CSR outcome-related studies only examine firm outcomes, not family and firm outcomes. Although there is much theorizing about family outcomes playing a significant role in family firm management, we could not identify any empirically-related findings.…”
Section: Introductionmentioning
confidence: 99%